Harmonizing The Values of Love and Tolerance in Combating Child Marriage - Nugroho, Irzak Yuliardy (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Child marriage remains a persistent issue in Probolinggo Regency, posing risks to children’s well-being and raising complex legal, religious, and socio-cultural challenges. This study aims to explore how the values of love and tolerance in Islamic law, along with local wisdom, can be harmonized to address the practice of child marriage. Employing a normative-empirical approach, the research analyzes classical and contemporary Islamic legal sources, especially through the lens of maqāṣid al-sharī‘ah and integrates field data gathered from interviews and observations. Findings reveal that child marriage in the region is often driven by economic hardship, cultural norms, and religious misinterpretation. Islamic law, when viewed contextually, offers a strong foundation for child protection as a central objective. Moreover, local wisdom that emphasizes social harmony, compassion, and deliberation serves as a potential entry point for legal reconstruction. The discussion proposes a model of harmonization between Islamic legal principles and cultural practices, rooted in love and tolerance, as a strategic solution to reduce child marriage. The study recommends community-based legal education that integrates religious values and cultural sensitivity to prevent child marriage effectively.